The Urgency of the Sirri Marriage Pre-Marriage Agreement Regarding Joint Property - Nurzannah Nurzannah; Wahda Z. Imam; Faissal Malik (Journal of Social Science, 2023)
This study aims to analyze the urgency of the sirri marriage prenuptial agreement related to joint property and the form of legal protection of joint property in the marriage agreement. The research method used in this study is normative legal research as a process to find legal rules, legal principles, and legal doctrines to answer the legal issues faced. The results of this study show that the urgency of prenuptial agreements related to sirri marriage and joint property is that in prenuptial agreements, prospective married couples can arrange ownership and separation of property to avoid combining property obtained by each husband and wife during marriage.